2002
DOI: 10.1108/02651330210451935
|View full text |Cite
|
Sign up to set email alerts
|

The human values’ lenses of country of origin images

Abstract: By using a core element of culture, human values, the paper seeks to identify patterns in the way individuals perceive other countries and their products. Based on the above a conceptual framework and a set of hypotheses were developed. Variables such as direct contact with a country, fluency in a country's language as well as demographic differences are included as control variables. Results indicated that human values can predict better country of origin images than other variables. However, the predictive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
104
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 68 publications
(114 reference statements)
2
104
0
5
Order By: Relevance
“…The results observed with demographic variables are consistent with those reported by Balabanis et al (2002) who found that demographic variables had little effect on the evaluation of COO Germany in their Czech and Turkish samples. Samiee et al (2005) also reported a small contribution of demographic variables in explaining COO perceptions.…”
Section: Analyses Of Variance Of Country Perceptionssupporting
confidence: 90%
See 1 more Smart Citation
“…The results observed with demographic variables are consistent with those reported by Balabanis et al (2002) who found that demographic variables had little effect on the evaluation of COO Germany in their Czech and Turkish samples. Samiee et al (2005) also reported a small contribution of demographic variables in explaining COO perceptions.…”
Section: Analyses Of Variance Of Country Perceptionssupporting
confidence: 90%
“…Although some research has linked the evaluation of countries of origin to antecedents and moderators such as the familiarity with a country, demographic characteristics, shopping behaviour, attitudes and human values (Balabanis et al, 2002;Hsieh et al, 2004;Kucukemiroglu et al, 2005;Samiee et al, 2005;Wall et al, 1991), or manufacturing dimensions such as COD and COA (Insch and McBride, 2004) across products of varying degree of complexity, little is known about how these variables jointly work in a multinational setting. Understanding how country evaluations are related to the product and manufacturing dimensions of a COO and antecedents such as demographics, and personal traits, and moderators such as product familiarity and shopping behaviour across a variety of nations may help international marketing researchers to better understand the contributing factors underlying the formation of COO evaluations and how these vary across nations.…”
mentioning
confidence: 99%
“…Junto ao estereótipo nacional está a imagem de país, definida como o conjunto de crenças e de impressões sobre uma determinada nação, incorporando crenças e avaliações cognitivas e afetivas (BALABANIS; MUEL-LER; MELEWAR, 2002;WHITE, 2012 A formação dos estereótipos de país se dá por meio da experiência direta, difusão de informações e do conhecimento e da exposição destes conteúdos na mídia de maneira indireta, podendo provocar no indivíduo processos cognitivos pelos quais o estereótipo opera como um atalho para simplificar uma interação complexa e processos afetivos intrínsecos (ASKEGAARD; GER, 1998) (HYNES et al, 2014).…”
Section: Estereótipos E a Imagem Do Paísunclassified
“…They also consider country affectdimension as the general emotion about the whole country, such as positive or negative ). Balabanis et al (2002) and Verlegh and Steenkamp (1999) also considered cognitive dimension as a cue of product quality and affective dimension as symbolic and emotional value of country of origin to customers.Perhaps the best definition given for country image is the one offered by Lu Wang et al (2012), which refers to both cognitive and emotional image of country. He believes that country image refers to the mental representation of a country and its people, including cognitive believes of the country`s economic and technological development stages, as well as the affective evaluations of its social and political systems or standpoints and affective country image refers to consumer affective evaluations (i.e., to like or dislike, be positive or negative) regarding a country and its people (Wang, Li, Barnes, & Ahn, 2012).…”
Section: Country Of Origin Imagementioning
confidence: 99%